IMF voting reform : need, opportunity and options - Woodward, David (UN New YorkUS, 2007)
Assesses the alternative options available for voting reform in the IMF from the perspective of developing countries, as a first step towards establishing a common developing country position in the current (and future) Quota Reviews.